2012
DOI: 10.5014/ajot.2012.002691
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Habilitation Therapy for Children With Fetal Alcohol Spectrum Disorders: An Adaptation of the Alert Program®

Abstract: These findings yield promising evidence of the effectiveness of the neurocognitive habilitation intervention in improving executive functioning and emotional problem solving in children with FAS or ARND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 23 publications
(13 reference statements)
3
101
0
1
Order By: Relevance
“…Of these studies, 21 met the inclusion criteria. Over half of these studies used experimental or quasi-experimental methods (Bertrand, 2009;Coles, Kable, & Taddeo, 2009;Engle, 2008;Kable, Coles, & Taddeo, 2007;Keil, Paley, Frankel, & O'Connor, 2010;Kerns, Macsween, Wekken, & Gruppuso, 2010;Loomes, Rasmussen, Pei, Manji, & Andrew, 2008;O'Connor et al, 2012;Roebuck-Spencer & Mattson, 2004;Vernescu, 2007;Wells, Chasnoff, Schmidt, Telford, & Schwartz, 2012). Qualitative studies used purposeful sampling (Carpenter, 2011) and included a case study (Duquette, Stodel, Fullarton, & Hagglund, 2006) and pilot study (Grant et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these studies, 21 met the inclusion criteria. Over half of these studies used experimental or quasi-experimental methods (Bertrand, 2009;Coles, Kable, & Taddeo, 2009;Engle, 2008;Kable, Coles, & Taddeo, 2007;Keil, Paley, Frankel, & O'Connor, 2010;Kerns, Macsween, Wekken, & Gruppuso, 2010;Loomes, Rasmussen, Pei, Manji, & Andrew, 2008;O'Connor et al, 2012;Roebuck-Spencer & Mattson, 2004;Vernescu, 2007;Wells, Chasnoff, Schmidt, Telford, & Schwartz, 2012). Qualitative studies used purposeful sampling (Carpenter, 2011) and included a case study (Duquette, Stodel, Fullarton, & Hagglund, 2006) and pilot study (Grant et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study has shown improvements in executive functioning skills (e.g. memory, cause and effect, and problem solving) for children with FASD (Wells et al, 2012).…”
Section: Cognitive Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Wells et al [22] studied the efficacy of the neurocognitive habilitation intervention (based on the Alert Program®) focusing on self-regulation among 40 children (aged 6 to 11 years) with FASD. These researchers found that the intervention led to significant improvements in emotional functioning and parent-rated executive functional behaviors in a treatment group compared to a nointervention control group with prenatal alcohol exposure (n=38).…”
Section: Self-regulationmentioning
confidence: 99%